2022
DOI: 10.1039/d2ob01970a
|View full text |Cite|
|
Sign up to set email alerts
|

An asymmetric metal-templated route to amino acids with an isoquinolone coreviaa Rh(iii)-catalyzed coupling of aryl hydroxamates with chiral propargylglycine Ni(ii) complexes

Abstract: A general protocol for the asymmetric synthesis of artificial amino acids (AAs) comprising an isoquinolone skeletal was successfully elaborated via a straightforward Rh(III)-catalyzed C−H activation/annulation of various aryl hydroxamates with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…9-12 Besides, in the case of a largescale synthesis, it is possible to isolate the Ni(II) salt as well, either by complexation with EDTA 15 or via ion-exchange chromatography. [9][10][11][12] The structure and absolute configuration of the minor diastereomer of AA (2S,4S)-5 was unambiguously established via single-crystal XRD analysis (Fig. 3).…”
Section: Communicationmentioning
confidence: 99%
See 3 more Smart Citations
“…9-12 Besides, in the case of a largescale synthesis, it is possible to isolate the Ni(II) salt as well, either by complexation with EDTA 15 or via ion-exchange chromatography. [9][10][11][12] The structure and absolute configuration of the minor diastereomer of AA (2S,4S)-5 was unambiguously established via single-crystal XRD analysis (Fig. 3).…”
Section: Communicationmentioning
confidence: 99%
“…Initially, we tested the coupling of readily available chiral Ni( ii ) complex ( S , S )- 1a based on ( S )-allylglycine (the complex was synthesized via diastereoselective alkylation, 11 a see the ESI‡ for synthetic details) with phenyl hydroxamate 2a under conditions similar to those described in our previous report for propargyl derivatives. 12 It was found that the reaction catalyzed by pentamethylcyclopentadienyl rhodium complex [Cp*RhCl 2 ] 2 (at 2.0 mol% loading) with addition of CsOAc (2 equiv.) in methanol smoothly proceeds at room temperature with excellent regioselectivity, giving only 3-substituted 3,4-dihydroisoquinolone derivatives as a mixture of diastereomers ( S , S , R )- 3aa and ( S , S , S )- 3aa in a ratio of 2.9 : 1 with 90% combined yield (Table 1, entry 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, Belokon’s group made early pioneering contributions to the asymmetric metal-templated synthesis of amino acids. The groups of Saghyan, Larionov, and Magdesieva also fruitfully work in this field. In recent years, our group has made considerable efforts and reported several efficient protocols to obtain N , C -unprotected α- and β-amino acids in an enantiopure form using metal complexes, including Ni­(II) complexes and Cu­(II) complexes. However, the methods for Ni­(II) complexes required relatively high reaction temperatures or prolonged reaction time at room temperature, which led to low reaction efficiency . As for the resolution method via Cu­(II) complexes, the limitation is the inability to achieve configurational interconversion of α-amino acids and dynamic resolution of the racemic α-amino acids.…”
Section: Introductionmentioning
confidence: 99%